2014
DOI: 10.1002/qua.24651
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase water activation by Th atom: Reaction mechanisms and topological analysis

Abstract: Density functional theory calculations were performed to investigate the gas-phase reaction of Th atom with water. Three reaction pathways were identified, which leads to the formation of ThOH 1 H, ThO 1 H 2 , and H 2 ThO. The latter two are generated via the intermediate HThOH, and the H 2 ThO specie is generated from the isomerization of the HThOH intermediate. A thorough description of the reaction mechanism taking into account different possible spin states together with analysis of the electronic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The analyses of our calculations indicated that Pu + H 2 O and Th + H 2 O have similar mechanisms, [51] which are also similar to the insertion mechanism for the actinide cations. [6,14] However, despite this qualitative similarity, the Pu + H 2 O reaction had its own characteristics.…”
Section: Reaction Mechanismssupporting
confidence: 58%
“…The analyses of our calculations indicated that Pu + H 2 O and Th + H 2 O have similar mechanisms, [51] which are also similar to the insertion mechanism for the actinide cations. [6,14] However, despite this qualitative similarity, the Pu + H 2 O reaction had its own characteristics.…”
Section: Reaction Mechanismssupporting
confidence: 58%
“…A large ELF value at a point (the redder area) is considered where electrons are greatly localized around it, suggesting that there may be covalent bond, lone pair, or atomic inner shell . Aside from ELF, the AIM analysis of the bond critical points (BCPs) method also has proven to be a very useful tool for studying chemical bonds . The presence of a BCP, the electron density ( ρ ) as well as its Laplacian (△ 2 ρ ) at BCP are the topological properties of a bond.…”
Section: Methodsmentioning
confidence: 99%
“…[57] Aside from ELF, the AIM analysis of the bond critical points (BCPs) method also has proven to be a very useful tool for studying chemical bonds. [58][59][60] The presence of a BCP, the electron density (ρ) as well as its Laplacian (5 2 ρ) at BCP are the topological properties of a bond. Negative and positive values of 5 2 ρ(BCP) indicate that electron density is locally concentrated and depleted, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, LOL has the same value range with ELF [0, 1]. Aside from LOL, AIM analysis by the bond critical points (BCPs) method was performed for describing the chemical bonds . The topological properties of a bond mainly consists of the BCP, corresponding electron density ( ρ [BCP]) and its Laplacian ∇ 2 ρ (BCP).…”
Section: Methodsmentioning
confidence: 99%
“…Aside from LOL, AIM analysis by the bond critical points (BCPs) method was performed for describing the chemical bonds. [49,50] The topological properties of a bond mainly consists of the BCP, corresponding electron density (ρ[BCP]) and its Laplacian r 2 ρ(BCP). Positive and negative values of r 2 ρ(BCP) denote that electron density is sparse and dense, respectively.…”
Section: Methodsmentioning
confidence: 99%